2021
DOI: 10.1177/10935266211046996
|View full text |Cite
|
Sign up to set email alerts
|

Secretory Carcinoma in Children and Young Adults: A Case Series

Abstract: Secretory carcinoma (SC), previously known as mammary analogue secretory carcinoma, is a rare salivary gland neoplasm that typically presents as a slow-growing painless lesion in the head and neck. SC occurs mainly in adults but has been described in children with the youngest reported patient diagnosed at five years of age. In children the gender distribution has been reported as female to male ratio of 1:1.2. SC is generally considered a low-grade malignancy with characteristic morphological features and imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Therefore, we can speculate that male SBC is more likely to occur at a younger age than is female SBC. Notably, in the small series composed exclusively of pediatric and adolescent patients, males also were the majority among pediatric patients with predominantly low-grade and early-stage tumors (12). Interestingly, the incidence of SBC has been declining in recent decades, which may be related to the reduction of the misdiagnosis rate resulting from the enhanced understanding of SBC and the improvement of diagnostic technology (8).…”
Section: Demographic Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we can speculate that male SBC is more likely to occur at a younger age than is female SBC. Notably, in the small series composed exclusively of pediatric and adolescent patients, males also were the majority among pediatric patients with predominantly low-grade and early-stage tumors (12). Interestingly, the incidence of SBC has been declining in recent decades, which may be related to the reduction of the misdiagnosis rate resulting from the enhanced understanding of SBC and the improvement of diagnostic technology (8).…”
Section: Demographic Characteristicsmentioning
confidence: 99%
“…Therefore, we can speculate that male SBC is more likely to occur at a younger age than is female SBC. Notably, in the small series composed exclusively of pediatric and adolescent patients, males also were the majority among pediatric patients with predominantly low-grade and early-stage tumors ( 12 ).…”
Section: Demographic Characteristicsmentioning
confidence: 99%
“…Out of a total of 226 studies published between 2010 and 2023, identified at initial search and screened for retrieval, 112 1–3,6–114 articles were included in the study, with a total of 674 patients described in these articles. The identification and screening process is described in Figure 1.…”
Section: Resultsmentioning
confidence: 99%